2022
DOI: 10.33546/bnj.2106
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between caregiving stress and sleep quality among family caregivers of older adults with dementia in Thailand

Abstract: Background: Providing care for older people with memory loss is a significantly stressful task. The caregiver experienced deterioration of the care recipients regarding their cognitive and functioning abilities, often resulting in the caregiver’s feelings of distress, stress, and unsatisfactory sleep quality.  Objective: This cross-sectional study aimed to examine the relationships between caregiving stress and sleep quality among family caregivers of older adults with dementia.  Methods: A simple random sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…The self-administrated RSS covers various aspects of burden, such as subjective emotional responses, restrictions on the social life of the nextof-kin, and negative feelings associated with the dementia sufferers and their behaviour. The result of the factor analysis turned out to be identical to those performed 40 years ago in Britain [20], 15 years ago in Norway [23], and recently in Germany [38] and Thailand [32], which displays the usefulness of the scale over time and across cultures. Being a next-ofkin carer of someone suffering from dementia of any aetiology is stressful [15][16][17][18][19][39][40][41][42][43][44].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The self-administrated RSS covers various aspects of burden, such as subjective emotional responses, restrictions on the social life of the nextof-kin, and negative feelings associated with the dementia sufferers and their behaviour. The result of the factor analysis turned out to be identical to those performed 40 years ago in Britain [20], 15 years ago in Norway [23], and recently in Germany [38] and Thailand [32], which displays the usefulness of the scale over time and across cultures. Being a next-ofkin carer of someone suffering from dementia of any aetiology is stressful [15][16][17][18][19][39][40][41][42][43][44].…”
Section: Discussionsupporting
confidence: 70%
“…One observation we made during the theoretical analysis of RSS as the screen instrument is the discovery of different approaches to defining the term ‘relative’. While Scandinavia uses the term ‘relatives’ stress scale [ 24 , 26 , 27 , 28 , 30 ], which can only be taken as meaning ‘a family member’, Anglo-Saxon and eastern cultures use the term ‘relative’ stress scale [ 31 , 32 , 33 ], presumably meaning that the stresses are in comparison—relative—to each other, thus focussing the attention on the role of the relative and the stress they feel [ 34 ]. In this study, we have used the term ‘RSS’ to mean ‘Relatives’ Stress Scale’.…”
Section: Methodsmentioning
confidence: 99%
“…Total scores range from 0 to 60, with a higher score indicating a higher degree of stress. The RSS was translated from the original English version to the Thai language by Sanprakhon et al 8 They reported a content validity index of 0.92 and Cronbach’s alpha coefficient of 0.87 for internal reliability. In our study, Cronbach’s alpha was 0.87.…”
Section: Methodsmentioning
confidence: 99%
“…The scale has been used to measure caregiver stress, was available in the Thai language, and was used successfully in the pilot study. 8,18 The 15-item RSS has 3 dimensions: personal distress, degree of life upset, and negative feelings toward the person with dementia. Participants rate the frequency or severity of their stress on a five-point scale scored 0 to 4 (e.g., "never," "rarely," "sometimes," "frequently," and "always").…”
Section: Study Outcomesmentioning
confidence: 99%
See 1 more Smart Citation